Punctuation Errors of Adult Native Russian Speakers and Psycholinguistics (Dash between Subject and Predicate) - K. Ya. Seagal (Научный диалог, 2023)
The problem of psycholinguistic interpretation (from the point of view of the writer) of punctuation errors is considered. The material for the study was punctuation errors in the punctogram “Dash between the subject and the predicate” and their explanations obtained from adult subjects (from 22 to 30 years old) as part of a “natural” experiment. The relevance of the study lies, firstly, in the psycholinguistic “turn” in the study of punctuation errors; secondly, in the development of the concept of punctuation as a special component in the generation of a written utterance. It is shown that punctuation errors associated with the omission of a dash or with the use of a comma instead of it in the position between the nominative/ infinitive subject and the predicate with a zero copula are mainly due to the overgeneralization of the model conditions for the use of a dash. The author explains that the punctuation component is created by punctuation skills acquired in the learning process and is a system of speech actions (and operations) that allow using a punctogram or a punctuation mark in accordance with the norm, usage and intentions of the writer. The analysis of punctuation errors comes to the conclusion that the punctuation component, on the one hand, is distributed between the late phases of inner speech and external speech, and on the other hand, belongs not only to the model of generating a separate written utterance, but also to the model of generating a written text.